TUMOR MARKERS - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Tursunov Feruz Uktamovich; Aslamova Kumushbonu Jalil qizi (TADQIQOTLAR.UZ, 2024)
Annotation. In order to assess the effectiveness of treatment, identify residual and recurrent tumors, diagnose and predict the tumor process, the article presents data on the immunodiagnosis of tumors using tumor markers. A special place in the diagnosis of tumors is occupied by the determination of the increase in blood serum of tumor markers, the increase of which in the blood serum is associated with the development of tumor processes of various origins. The main methods that determine the level of tumor markers in peripheral blood are enzyme-linked immunosorbent and chemiluminescent immunoassays.